Análise espaço- temporal de chuvas na Paraíba utilizando estimativas do satélite TRMM - Costa, Samir Gonçalves Fernandes (2017)
With the improvement of remote sensing techniques the use of satellite has been an increasingly common alternative in the monitoring and space-time analysis of precipitation against spatial limitation, collection errors and data discontinuities that are common to conventional measurement methodology. Taking this into account and the fact that in the last two decades the area of study has suffered a serious water crisis. The objective of this work was to analyse the spatial-temporal behavior of rainfall over the state of Paraíba from 1998 to 2015, based on the daily precipitation estimates of Tropical Rainfall Measuring Mission (TRMM) satellite 3B42-v.7. For this, the precipitation data were submitted to the non-parametric tests MannKendall and Sen, the method of analysis of clusters Average Linkage and the interpolator space Spline regularized. When analysing the results, it was verified that in a third of the years the values of the annual precipitation were below the average of the period and that the altimetry was shown to be influential in certain localities of the study area. In the evaluation of trends in precipitation there were no levels of significance that could confirm the hypothesis of trends in the annual and seasonal precipitation of the summer and fall seasons. However, it was observed the presence of significant trends with statistical confidence of 90% in the precipitation of the winter and spring seasons, revealing according to cluster analysis a greater similarity in the behavior of the annual precipitation in TRMM points that formed regions in the part of the Agreste Paraibano and Mata Paraibana, with the seasons summer and autumn indicating a greater correlation in the values of precipitation than in the winter seasons and spring. Regarding the analyses of the maximum number of Consecutive Dry Days (CDD) and Consecutive Wet Days (CWD), it was noticed that although the year 2012 was the driest in the analysed period, it did not necessarily present the highest number of days consecutive dry seasons, while the year 2000, even though it was the most rainy season, there were no fewer consecutive dry days this year. In addition, it was evidenced a prevalence of extreme events of CDD and CWD in Mata Paraibana and Agreste, which according to the verified levels of significance can confirm the trend hypothesis with a statistical confidence higher than 90% for an increase in the number of consecutive dry days and a stability in the number of consecutive wet days in these regions. Regarding the clusters analysis performed on the CDD and CWD index values, it was observed that although the correlation coefficients were low, the results indicated that there was a greater similarity in the occurrence of consecutive wet days events than of consecutive dry days between the TRMM points of the study area, with a decrease in the similarity of behavior of both from west to east. Considering these results, it can be concluded that the TRMM satellite proved to be effective in the space-time analysis of precipitation and the methodologies and information produced in this work can be used by the water resources management bodies for the purposes of water monitoring in the state of Paraíba.